Development of a 3D cell printed structure as an alternative to autologs cartilage for auricular reconstruction. Issue 5 (28th February 2016) - Park, Ju Young; Choi, Yeong‐Jin; Shim, Jin‐Hyung; Park, Jeong Hun; Cho, Dong‐Woo
Abstract: Surgical technique using autologs cartilage is considered as the best treatment for cartilage tissue reconstruction, although the burdens of donor site morbidity and surgical complications still remain. The purpose of this study is to apply three‐dimensional (3D) cell printing to fabricate a tissue‐engineered graft, and evaluate its effects on cartilage reconstruction. A multihead tissue/organ building system is used to print cell‐printed scaffold (CPS), then assessed the effect of the CPS on cartilage regeneration in a rabbit ear. The cell viability and functionality of chondrocytes were significantly higher in CPS than in cell‐seeded scaffold (CSS) and cell‐seeded hybrid scaffold (CSHS) in vitro . CPS was then implanted into a rabbit ear that had an 8 mm‐diameter cartilage defect; at 3 months after implantation the CPS had fostered complete cartilage regeneration whereas CSS and autologs cartilage (AC) fostered only incomplete healing. This result demonstrates that cell printing technology can provide an appropriate environment in which encapsulated chondrocytes can survive and differentiate into cartilage tissue in vivo . Moreover, the effects of CPS on cartilage regeneration were even better than those of AC. Therefore, we confirmed the feasibility of CPS as an alternative to AC for auricular reconstruction. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1016–1028, 2017.